Publishers and digital advertising: plurality of formats - López Castro, Raquel; Valderrama Santomé, Mónica (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The press as media advertising has been transformed by adaptative problems to the digital language. The text explores the ways of boarding these changes in nine publishers: from digital natives to the national titles and regional coverage. It treats to prepare a complete and harmonized proposal, through a work of direct observation of the advertising formats with a comparative between the standard denominations and those used in the rates of the online press. The research sheds light on how much has been inherited from print media or the need for revision of the nomenclature.